(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2023)
The new book edited by Patricia Chiantera-Stutte and Giovanni Borgognone provides a rich and compelling analysis of the many narratives on, and around, “civilizations”, and how the latter concept continues to be used to support a variety of political agendas, from liberal democracy to ethno-nationalist authoritarianism.